The Structure of Myristoylated Mason-Pfizer Monkey Virus Matrix Protein and the Role of Phosphatidylinositol-(4,5)-Bisphosphate in Its Membrane Binding - Prchal, Jan (2012)
We determined the solution structure of myristoylated Mason-Pfizer monkey virus matrix protein by NMR spectroscopy. The myristoyl group is buried inside the protein and causes a slight reorientation of the helices. This reorientation leads to the creation of a binding site for phosphatidylinositols. The interaction between the matrix protein and phosphatidylinositols carrying C(8) fatty acid chains was monitored by observation of concentration-dependent chemical shift changes of the affected amino acid residues, a saturation transfer difference experiment and changes in (31)P chemical shifts. No differences in the binding mode or affinity were observed with differently phosphorylated phosphatidylinositols. The structure of the matrix protein–phosphatidylinositol-(4,5)-bisphosphate [PI(4,5)P(2)] complex was then calculated with HADDOCK software based on the intermolecular nuclear Overhauser enhancement contacts between the ligand and the matrix protein obtained from a (13)C-filtered/(13)C-edited nuclear Overhauser enhancement spectroscopy experiment. PI(4,5)P(2) binding was not strong enough for triggering of the myristoyl-switch. The structural changes of the myristoylated matrix protein were also found to result in a drop in the oligomerization capacity of the protein.